602 From Laptop to Laparotomy: A Retrospective Evaluation of Virtual Teaching Methods in Surgical Anatomy During COVID-19. (12th October 2021) - Paluch, A; Lakpriya, S; Moyes, S; Evans, L
Abstract: Introduction: Sound knowledge of anatomy is the cornerstone of safe surgical practice and COVID-19 has created new barriers to universally achieving this standard of education. There has been drastic change to the way in which anatomy education is delivered, with the loss of 'face-to-face' and 'hands-on' teaching methods creating unique challenges in a subject that relies on students' understanding of 3-D concepts. Globally, institutions have switched to online learning methods and student experience is vital in shaping this new landscape and optimising resources. Method: A retrospective, online survey distributed to a cohort of Year 2 BMBS students after a term of anatomy teaching during COVID. Results: 40 students participated in the survey. Qualitative feedback was largely positive towards online learning. Smaller groups and facilitator-led sessions, for example utilising virtual 'breakout rooms', were more favourable. Sessions based around clinical scenarios appeared the most popular, followed by those using an online quiz format and then those using virtual dissections on an anatomy app (63%, 39% and 18% of students rating each option respectively as 'extremely helpful'). Where feedback was negative, themes included a perceived lack of 3-D visual aids or 'real-life' anatomy and difficulty navigating the anatomy app used for virtual dissection. Conclusions: Small group sessions with a focus on clinical scenarios were the most popular. The ability to visualise structures in 3-D remains an important component of student experience. The challenge lies in simultaneously delivering new anatomical concepts while supporting students to adapt to the new technology that will enable this.